2005
DOI: 10.1152/japplphysiol.01183.2004
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of O2uptake, leg blood flow, and muscle deoxygenation are slowed in the upper compared with lower region of the moderate-intensity exercise domain

Abstract: (SD 4)] performed repetitions (6 -8) of twolegged, moderate-intensity, knee-extension exercise during two separate protocols that included step transitions from 3 W to 90% estimated lactate threshold ( L) performed as a single step (S3) and in two equal steps (S1, 3 W to ϳ45% L; S2, ϳ45% L to ϳ90% L). The time constants ( ) of pulmonary oxygen uptake (V O2), leg blood flow (LBF), heart rate (HR), and muscle deoxygenation (HHb) were greater (P Ͻ 0.05) in S2 ( V O2, ϳ52 s; LBF, ϳ 39 s; HR, ϳ42 s; HHb, ϳ33 s) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
110
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(129 citation statements)
references
References 41 publications
19
110
0
Order By: Relevance
“…Data from these studies are comparable to those of others (DeLorey et al 2003;Grassi et al 2003;MacPhee et al 2005). One of the limitations of using NIRS to evaluate StO 2m in skeletal muscle is that the sampling is not restricted to working muscle, but includes-in addition-skin, adipose tissue, capillaries, and small arterioles and venules.…”
Section: Measurement Limitationssupporting
confidence: 75%
See 1 more Smart Citation
“…Data from these studies are comparable to those of others (DeLorey et al 2003;Grassi et al 2003;MacPhee et al 2005). One of the limitations of using NIRS to evaluate StO 2m in skeletal muscle is that the sampling is not restricted to working muscle, but includes-in addition-skin, adipose tissue, capillaries, and small arterioles and venules.…”
Section: Measurement Limitationssupporting
confidence: 75%
“…In particular, near infrared spectroscopy (NIRS) can be used to monitor the relative concentrations of deoxyhemoglobin and deoxymyoglobin or tissue oxygen saturation, StO 2m , during dynamic exercise. In lieu of specific assessments of intracellular oxygenation, NIRS can provide information reflecting the balance between local muscle oxygen delivery and utilization within the interrogated tissue region (DeLorey et al 2003;Grassi et al 2003;MacPhee et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A limitation in O 2 delivery to the exercising muscle has been proposed as a likely mechanism regulating the rate of adaptation of oxidative phosphorylation (Murias et al, 2010(Murias et al, , 2011b(Murias et al, , 2014Poole et al, 2008;. It has been hypothesized (Phillips et al, 1995) that faster femoral artery blood velocity (from endurance training) was responsible for reductions in τVO 2p ; however, measures of muscle conduit artery blood flow kinetics in young healthy adults have shown that the rate of adjustment is similar to or faster than that of VO 2p (duManoir et al, 2010;MacPhee et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies that have provided some empirical evidence to oppose the use of τ (Hughson & Morrissey, 1982;Brittain et al, 2001;Koppo et al, 2004;MacPhee et al, 2005;Stirling et al, 2005), however they are limited and there lacks any strong empirical validation of the methods. Therefore, it felt necessary to reassess the pre-defined concepts of τ and 4τ as they apply to two contrasting subject groups, highly-trained and untrained.…”
Section: T1mentioning
confidence: 99%
“…However, even with its versatile use over the past four decades, the mono-exponential model has yet to be explicitly validated. This is all the more problematic when past research exists which questions the validity of using a simple mono-exponential model to explain V O2 kinetics behaviour (Linnarson, 1974;Hughson & Morrissey, 1982;Casaburi et al, 1989;Koppo et al, 2004;MacPhee et al, 2005;Stirling et al, 2005;McNulty et al, 2015).…”
Section: Introductionmentioning
confidence: 99%